Transformational Leadership: A Qualitative Analysis of Effective Leadership in Women’s Soccer in England - Rhind, Daniel J. A.; Hodson, Emily; Newman, James; Rumbold, James (Unisia, 2022)
This study examined perceptions of effective leadership in elite women’s soccer by team captains. Data were collected from a range of perspectives in four elite female soccer teams in England. For each of the four teams, data were collected from 6 participants (total N = 24 players). For each of the four teams, interviews were conducted with the captain and the coach as well as a focus group with 4 players regarding their perceptions of the captain’s leadership. Data were firstly deductively categorised under the four key areas of transformational leadership: idealised influence, inspirational motivation, individualised consideration and intellectual stimulation. An inductive analysis of the relevant data which did not fit into these themes revealed the importance of captains building bridges through helping to navigate the gender gap as well as to facilitate effective relationships with and between players. The implications of these findings are discussed.